Formulasi Bakteri Filosfer Padi dan Aplikasinya untuk Mengendalikan Penyakit Hawar Daun Bakteri - Siska Tridesianti; Alina Akhdiya; Aris Tri Wahyudi (Jurnal Fitopatologi Indonesia, 2016)
Xanthomonas oryzae pv.oryzae is a casual agent of bacterial leaf blight disease (BLB) of rice. The disease can infect every phases of plant growth and can reduce rice production. In the previous study we have isolated nonpathogenic phyllosphere bacteria against X. oryzae pv.oryzae. For further study, in the present work we developed the formulation of the phyllosphere bacteria and tested their effectiveness against BLB in greenhouse trials. Out of three alternative medium used in culturing bacterial cell biomass, it was revealed that potato broth served as the best medium in comparison with skim milk molasses and bran extract. Formulation of phyllosphere bacteria was conducted by using of talc as main carrier, i.e. approximately 109 cfu g-1of main carrier. Application of the formula on rice leaves indicated that BFV 60, BFF 69, BFR 203 and BFR 153 were the best formula for controlling BLB and were able to reduce disease incidence up to 40.73%, 39.72%, 39.26%, and 28.07%,  respectively